An Analysis of the Social Dimensions of Sustainable Urban Public Spaces with Emphasis on Users’ Perception (Case Study: El Goli Park, Tabriz) - Basiri, Mostafa (Management Strategies and Engineering Sciences, 2023)
Urban public spaces are one of the key elements of the social and physical structure of cities, which play an important role in improving the quality of life, spatial justice, and sustainable development. The aim of this study is to analyze the social dimensions of sustainable development of urban public spaces with an emphasis on user perceptions. The theoretical framework of the study is based on Henri Lefebvre’s theory of “social production of space,” which considers space to include three dimensions: perceived, Conceived, and lived in this regard, the indicators obtained based on the theorists' perspectives were used to measure different dimensions of space. The present study was conducted in the field using a Likert-scale questionnaire. The statistical population consisted of four groups of users of El Goli Park in who were selected by random sampling. The data were analyzed using descriptive statistical tests and the Kruskal-Wallis test in SPSS software. The results of the analysis indicate that users' evaluations of the three dimensions of space differ from each other. The highest rankings were assigned by residents in the perceived and conceived dimensions of space, followed closely by user's evaluation of the lived space dimension, and both experts and students had lower scores. These findings were consistent with Lefebvre's theory about the importance of lived experience, place belonging and social status in our perception of space. The authors point to the importance of engaging with the mental, emotional and social dimensions of space in public policymaking and design of public spaces, they also give several key recommendations for participatory design, improving the quality of life of space, and ongoing evaluation with a focus on user experience.